1992
DOI: 10.1182/blood.v80.1.134.bloodjournal801134
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin mediates Ca(2+)-dependent adhesion of activated platelets to many different types of leukocytes: detection by flow cytometry

Abstract: Previous studies have shown that thrombin-activated platelets interact through the P-selectin with neutrophils and monocytes. To identify other types of leukocytes capable of such an interaction, eosinophils, basophils, and lymphocytes were isolated from whole blood. Binding of these cells to activated platelets was examined in a double immunofluorescence assay and the results show that activated platelets not only bind to neutrophils and monocytes, but also to eosinophils, basophils, and subpopulations of T l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 27 publications
2
54
0
Order By: Relevance
“…Therefore, following ADP stimulation, the entire neutrophil population was found to express more CD11b/CD18, less CD62L, more antibody 24 binding sites, produce more superoxide and phagocytose more N. meningitidis. These results extend the Âźndings from previous studies which showed that platelet activation is a potent stimulus for both PNC formation and neutrophil function (Peters et al, 1997;de Bruijne Admiraal et al, 1992;Chignard & Renesto, 1994;Nagata et al, 1993).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, following ADP stimulation, the entire neutrophil population was found to express more CD11b/CD18, less CD62L, more antibody 24 binding sites, produce more superoxide and phagocytose more N. meningitidis. These results extend the Âźndings from previous studies which showed that platelet activation is a potent stimulus for both PNC formation and neutrophil function (Peters et al, 1997;de Bruijne Admiraal et al, 1992;Chignard & Renesto, 1994;Nagata et al, 1993).…”
Section: Discussionsupporting
confidence: 90%
“…These Âźndings are indicative that neutrophils within platelet±neutrophil complexes represent an activated subset of cells. In addition, it can be inferred that the platelet component of PNCs must also represent an activated subpopulation of platelets, as CD62P expression is an essential prerequisite for PNC formation (de Bruijne Admiraal et al, 1992;Evangelista et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils express seven integrins, a 4 b 1 (CD49d/ CD29), a 6 b 1 (CD49f/CD29), a L b 2 (CD11a/CD18), a M b 2 (CD11b/CD18), a X b 2 (CD11c/CD18), a D b 2 , and a 4 b 7 [5,12,13,41,42,55,128], which potentially interact with ligands including vascular cell adhesion molecule (VCAM)-1, ICAM-1, laminin, fibrinogen/fibrin, vitronectin, and periostin, on other cells or in the extracellular matrix (ECM) [41,42,67]. The platelet integrin a IIb b 3 (CD41/CD61) [147] is not synthesized by eosinophils [110] but can be detected by flow cytometry or immunofluorescence microscopy staining on a variable proportion of eosinophils (in humans and mice), due to association of platelets or platelet fragments with some of the cells [64,130,[148][149][150][151][152]; activated platelets are known to bind leucocytes via P-selectin [153]. Some workers have detected low levels of additional integrins, including a 2 b 1 (CD49b/CD29), which is also not synthesized by eosinophils [110], on the eosinophil surface [154][155][156]; this is similarly likely due to platelet 'satellitism'.…”
Section: Integrinsmentioning
confidence: 99%
“…Upon the activation of these cells by strong agonists, e.g. thrombin, histamine and inflammatory cytokines such as interleukin‐1 and tumour necrosis factor‐α, P‐selectin is expressed on endothelial cells and plays an important role in mediating rolling of leucocytes on the activated endothelial cells of the blood vessel wall in the early phases of inflammatory reactions [10]. Inhibition or loss of one or more selectins significantly attenuates rolling and emigration in several inflammatory models [4].…”
Section: Introductionmentioning
confidence: 99%